Treatment recommendations for patients with Waldenström macroglobulinemia (WM) and related disorders: IWWM-7 consensus - Dimopoulos, M.A.; Kastritis, E.; Owen, R.G.; Kyle, R.A.; Landgren, O.; Morra, E.; Leleu, X.; García-Sanz, R.; Munshi, N.; Anderson, K.C.; Terpos, E.; Ghobrial, I.M.; et al. (Blood, 2014)
Waldenström macroglobulinemia (WM) is a distinct B-cell lymphoproliferative disorder for which clearly defined criteria for the diagnosis, initiation of therapy, and treatment strategy have been proposed as part of the consensus panels of International Workshops on WM (IWWM). As part of the IWWM-7 and based on recently published and ongoing clinical trials, the panels updated treatment recommendations. Therapeutic strategy in WM should be based on individual patient and disease characteristics (age, comorbidities, need for rapid disease control, candidacy for autologous transplantation, cytopenias, IgM-related complications, hyperviscosity, and neuropathy). Mature data show that rituximab combinations with cyclophosphamide/ dexamethasone, bendamustine, or bortezomib/dexamethasone provided durable responses and are indicatedformostpatients. Newmonoclonalan-tibodies (ofatumumab), second-generation proteasome inhibitors (carfilzomib), mam-malian target of rapamycin inhibitors, and Bruton's tyrosine kinase inhibitors are promising and may expand future treatment options. A different regimen is typically recommended for relapsed or refractory disease. In selected patients with relapsed disease after long-lasting remission, reuse of a prior effective regimen may be appropriate. Autologous stem cell transplantation may be considered in young patients with chemosensitive disease and in newly diagnosed patients with very-high-risk features. Active enrollment of patients with WM in clinical trials is encouraged.